Reliable Comparison of Pnicogen, Chalcogen, and Halogen Bonds in Complexes of 6-OXF2-Fulvene (X = As, Sb, Se, Te, Be, I) With Three Electron Donors - Liu, Na; Li, Qingzhong; McDowell, Sean A. C. (Frontiers in Chemistry, 2020)
The pnicogen, chalcogen, and halogen bonds between 6-OXF2-fulvene (X = As, Sb, Se, Te, Br, and I) and three nitrogen-containing bases (FCN, HCN, and NH3) are compared. For each nitrogen base, the halogen bond is strongest, followed by the pnicogen bond, and the chalcogen bond is weakest. For each type of bond, the binding increases in the FCN < HCN < NH3 pattern. Both FCN and HCN engage in a bond with comparable strengths and the interaction energies of most bonds are less than -6 kcal/mol. However, the strongest base NH3 forms a much more stable complex, particularly for the halogen bond with the interaction energy going up to -18 kcal/mol. For the same type of interaction, its strength increases as the mass of the central X atom increases. These bonds are different in strength, but all of them are dominated by the electrostatic interaction, with the polarization contribution important for the stronger interaction. The presence of these bonds changes the geometries of 6-OXF2-fulvene, particularly for the halogen bond formed by NH3, where the F-X-F arrangement is almost vertical to the fulvene ring.